BIOGRAPHY WORK: TRANSLATING MEANING THROUGH PAINTING PRACTICE IN A HUMANISTIC FRAMEWORK - Techawong, Ronnaphob; Apirating, Preechawut; Plengdeesakul, Burin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background and Objectives: This study aims to 1) examine artists’ biographies through an anthroposophical approach and 2) analyze the process of meaning interpretation in painting. The study focuses on three artists: Caspar David Friedrich, Odilon Redon, and Pablo Picasso, the research investigates the relationships among life experiences, environmental conditions, significant life events across different stages of life, and socio-cultural contexts that influence transformations in artistic form and content throughout the artists’ lifetimes. Methods: This study adopts a qualitative research methodology. The selected artists were selected based on shared biographical characteristics, visual artistic features, and emotional expressions reflected in their works. The research integrates biographical analysis with the examination of paintings in terms of sign systems, compositional structures, and color theory. The analytical framework is grounded in the anthroposophical philosophy of Rudolf Steiner, in conjunction with the process philosophy of Alfred North Whitehead, to interpret how lived experiences are transformed into visual language. Results: The findings reveal that painting is not merely a representation of objective reality, but a process of meaning transformation that connects between the artist’s inner and outer worlds. This process is articulated through key elements, including painting style, composition, sign systems, color, and spatial treatment, which reflect conditions of fragmentation, deterioration, and abstract modes of perception. Furthermore, the study identifies shared characteristics among the three artists, particularly their engagement in deep introspection alongside outward observation, resulting in symbolic communication through visual forms and material representation. Application of this study: As part of the creative component, the researcher produced six series of paintings derived from the process of meaning interpretation. These works demonstrate a transdisciplinary integration of anthroposophy, process philosophy, and art therapy. The findings can be applied as a framework for analyzing and creating contemporary artworks, as well as for developing art education practices and practice-based research that connect lived experience with artistic production. Conclusions: The study highlights that biographical inquiry within an anthroposophical framework serves as a significant tool for deepening the understanding of the relationship between life, art, and human perception. It also contributes to the development of new knowledge in art studies by integrating biographical analysis with artistic practice, offering expanded perspectives in contemporary art contexts.